Review of Electrical and Thermal Modeling Techniques for Three-Phase PMSM Drives - Azom, Md Ali; Hossain, Md. Shahen; Khan, Md. Yakub Ali (Peneliti Teknologi Teknik Indonesia, 2025)
The objective of this paper is to present a thorough examination of electrical and thermal modelling approaches for three-phase PMSM drives, emphasizing their methods, potential, and constraints. Modern electric drives now rely heavily on Permanent Magnet Synchronous Motors (PMSMs), which are found in renewable energy systems, industrial automation, and electric cars. PMSM drives must be accurately modelled to maximize performance, guarantee dependability, and increase operational longevity. The methods, advantages, and disadvantages of electrical and thermal modelling approaches for three-phase PMSMs are thoroughly examined in this paper. To forecast electromagnetic behavior and drive efficiency, the electrical modelling section examines dynamic dq-axis transformations, finite element methods (FEM), equivalent circuit models, and sophisticated AI-driven techniques. The function of thermal modelling tools in controlling heat dissipation and halting thermal degradation is examined. These techniques include lumped parameter models, coupled electro-thermal models, and computational fluid dynamics (CFD). The trade-offs between these models' practical usability, computational complexity, and accuracy are highlighted by a comparative comparison. Incorporating trade-offs between accuracy, complexity, and usability into modelling methods for three-phase Permanent Magnet Synchronous Motor (PMSM) drives offer a comprehensive viewpoint that strikes a compromise between performance and usefulness. Current issues are noted in the review, including the requirement for real-time adaptive models and the incorporation of multi-physics effects. New developments are highlighted as promising paths to improve PMSM modelling, including AI-based simulations and digital twin technologies. The goal of this study is to provide researchers and engineers with a thorough resource that will direct the creation of reliable and effective PMSM drive systems. The review's findings and insights have the potential to influence a variety of applications, spur innovation in PMSM drives, and aid in the global shift to sustainable technologies and electrification.